Hybrid Approach for Website Quality Evaluation: Linear Weightage Model and Fuzzy Analytical Hierarchy Process - JATI, HANDARU (2010)
In rece~t years, many people have devoted their efforts to the issue of quality of website. The ',concept of quality is consisting of many criteria: quality of service ' perspective, a user perspective, a content perspective or indeed ,a usability perspective. The very spec,ial nature of the web applications and website' pose unique software testing challen'g es. Webmasters, Web applications developers, and Website quality assurance managers need tools and methods that can match up to the new needs. The result of this study confirmed that criteria of website quality consist of eleven criteria I (load time, response time, page rank, frequency of update, traffic,;, design optimization, size, nu mber of ite\ns, accessibility error, markup validation, and broken link). Online diagnostic tools 'provided in the internet can be used to measure V)'ebsite quality related with criteria that' was determined in this research. This decreases the economic and noneconomic cost for conducting website evaluation. Online diagn9stics tools allow the website designer or researcher to evaluate many websites and to detect potential problems as well' as actual problems. This research conducts some tests to measure the ' quality website of Asian countries via web diagnostic tools on.line. The researcher proposes a methqdology for determining and evaluating the best e-government, Asian ' airlines, and Malaysian universities sites based on many criteria, of website quality. Applying Hybrid model between LWM and F AHP approach for website evaluation has resulted in significant acceleration of implementation, raised the overall effectiveness ' with respect to the underlying methodology and ultimately enabled more efficient procedure. The result of this study confirmed most of Asian web~ites are neglecting performance and airlines websites have the best quality performancre based on Hybrid Model Evaluation. According to the results of the evaluation process, Airlines sector has ' the highest average. score compare to e-govemment and university. Keywords:-performance, quality, website, Hybrid model.In compliance with the terms of the Copyright Act 1987 and the IP Policy of the university, the copyright of this thesis has been reassigned by the author to the legal entity of the university, Institute of Technology PETRONAS Sdn Bhd. Due acknowledgement shall always be made of the use of any material contained in, or derived from, this thesis. © Handaru Jati, 2010 Institute of Technology PETRONAS Sdn Bhd All rights reserved. vii